Evaluación in vitro del efecto de nuevas Tiazolidinonas sobre la invasión y crecimiento del parásito Toxoplasma gondii (2020)
Conventional treatment for toxoplasmosis is a mix of pyrimethamine and sulfadiazine but this chemotherapy has severe side effects. Recent findings on the biological activity of the 4 thiazolidinones and taking into account the lack of effective medications used in the treatment of toxoplasmosis, in addition to the numerous side effects of pyrimethamine, led us to design and to synthesize new 5-aryliden 4- thiazolidinone and 2 hydrazono-4-thiazolidinone derivatives. In present work we first performed a bioinformatic analysis of molecular docking between thiazolidinones and protein kinase ROP18 and calmodulin of Toxoplasma gondii. Then, we evaluate the in vitro growth effect in T. gondii of 26 new compounds derived from 4- thiazolidinone was evaluated. To identify the growth rates of T.